2011
DOI: 10.1002/anie.201102967
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acyl Protein Thioesterases 1 and 2 as the Cellular Targets of the Ras‐Signaling Modulators Palmostatin B and M

Abstract: Finding the target: activity-based proteomic profiling probes based on the depalmitoylation inhibitors palmostatin B and M have been synthesized and were found to target acyl protein thioesterase 1 (APT1) and 2 (APT2) in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 26 publications
1
65
0
Order By: Relevance
“…Palmostatin M inhibits the eukaryotic hydrolase enzymes APT1 and APT2 by blocking their Ras GTPase depalmitoylation activity and in turn altering Ras GTPase localization and activity [26,27]. The β-lactone Palmostatin M may also have off-target effects on bacterial serine hydrolases with a similar active site.…”
Section: Resultsmentioning
confidence: 99%
“…Palmostatin M inhibits the eukaryotic hydrolase enzymes APT1 and APT2 by blocking their Ras GTPase depalmitoylation activity and in turn altering Ras GTPase localization and activity [26,27]. The β-lactone Palmostatin M may also have off-target effects on bacterial serine hydrolases with a similar active site.…”
Section: Resultsmentioning
confidence: 99%
“…A PT2 has also been reported to depalmitoylate H-Ras like APT1. However, it has more efficient catalytic activity than APT1 in depalmitoylating a biologically active semisynthetic N-Ras in vitro [105]. Overexpression of APT2, but not APT1, causes rapid depalmitoylation of the GAP-43 [106], demonstrating the substrate specificity of APT2.…”
Section: Acyl Protein Thioesterase 1 (Apts)mentioning
confidence: 99%
“…Interestingly, siRNA knockdown of APT1 did not statistically alter the ratio of golgi to plasma membrane NRas. This suggests either insufficient APT1 knockdown, or that Palmostatin B inhibits other protein thioesterases, such as APT2 ( K i = 34 nM) 18 that may contribute to NRas processing. Further experiments showed that addition of 30 - 100 µM of Palmostatin B dose-dependently impedes the growth of HRas or NRas transduced hematopoietic cells, but does not affect cells transduced with a non-palmitoylated isoform of KRas 29 .…”
Section: β-Lactonesmentioning
confidence: 99%
“…Palmostatin M similarly induces NRas mis-localization from the plasma membrane and partially restores E-Cadherin localization at cell-cell junctions in HRas-transformed MDCK cells 38 . Because β-lactones form a semi-stable covalent complex with their targets, an alkynyl Palmostatin M analogue was synthesized to annotate potential cellular targets 18 . Lysates were labeled with the alkynyl probes, conjugated to a tri-functional rhodamine/biotin-azide by copper-catalyzed click chemistry, enriched with streptavidin, and analyzed by in-gel fluorescence or mass spectrometry to identify candidate target proteins.…”
Section: β-Lactonesmentioning
confidence: 99%
See 1 more Smart Citation